2016
DOI: 10.1590/s1984-29612016025
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic efficiency of doramectin, fenbendazole, and nitroxynil, in combination or individually, in sheep worm control

Abstract: The anthelmintic efficiency of doramectin, fenbendazole, and nitroxynil, used individually or in combination, was determined by the Fecal Egg Count Reduction (FECR) test and cultivation of larvae of anthelminthic-treated sheep grouped as follows: G1 (doramectin), G2 (fenbendazole), G3 (nitroxynil), G4 (doramectin + fenbendazole), G5 (doramectin + nitroxynil), G6 (fenbendazole + nitroxynil), G7 (doramectin + nitroxynil + fenbendazole), G8 (untreated). In addition to individually used doramectin and fenbendazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
6
0
5
Order By: Relevance
“…The efficacies were categorized as: highly effective when Efficacy % > 98%; effective when 90-98%; moderately effective 80-89%; and insufficiently effective < 80% (Ordination 79/1996MERCOSUL, GMC, 1996: In Holsback et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacies were categorized as: highly effective when Efficacy % > 98%; effective when 90-98%; moderately effective 80-89%; and insufficiently effective < 80% (Ordination 79/1996MERCOSUL, GMC, 1996: In Holsback et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation exists for domestic livestock, a problem in developing and developed regions of the world, where infection with helminth parasites takes a tremendous toll on productivity (e.g., meat yields), 11 and resistance to anthelminthics is increasing alarmingly. 12 Thus, while helminth biology may be unfamiliar to the reader, helminths are a ubiquitous component of our ecosystem.…”
Section: Helminth Parasitesmentioning
confidence: 99%
“…Epidemiological studies of parasitic diseases in the North Pioneer mesoregion are scarce. However, the few studies on ruminants in this region have shown high parasite loads, which may reflect poor sanitary conditions and inadequate handling of these animals (HOLSBACK et al, 2013(HOLSBACK et al, , 2015(HOLSBACK et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%